Tangential Points: Aleksandr Bogdanov and Sergei Eisenstein Revisited - Tikka Pia (Cultural Science)
In the newly founded Soviet Union, Aleksandr A. Bogdanov and Segei M. Eisenstein, each in his own way, struggled to make sense of the world by means of the most recent findings in the sciences. Both were driven by a desire to describe the universal laws of organization that would embrace the dynamics of the human mind and society, mutually, in arts and sciences. Bogdanov, a leading theoretician of political, economical, cultural, and educational revolution, is today also recognized internationally as one of the pioneering systems scientists of the early twentieth century. Eisenstein began to establish an international reputation thanks to the originality of his films and his eclectic theoretical writings that have remained a rich source of continuing discoveries for film scholars. I propose that both of these thinkers, in their own right, and by way of their common synergy, can contribute to a systemic understanding of today’s complex world and its cultural reflections.